A Strategic Analysis of Urban Renewal in Taipei City Using Game Theory. (June 2014) - Lin, Yu-Chih; Lin, Feng-Tyan
One of the difficult tasks in urban renewal is land assembly because it requires consent from landowners. The major obstacle for negotiation comes from the fact that some landowners ask higher than market price for their land. The characteristics of landowners are classified into two types according to prospect theory. This study adopts game theory to analyze strategic interaction and negotiation processes between a developer and landowners in Taiwan. The aim of this study is to show the impact of the characteristics of landowners on the implementation of the project and the best strategy for developers to deal with the uncertainty of landowners' characteristics. We found that not only the characteristics of the landowners, but also the strategies adopted by a developer may hinder the implementation of an urban renewal plan.